THE EMERGENCE OF STATES IN WORLD HISTORY - Ikromova Marhabo Muzaffar kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article analyzes in detail the historical development of the concept of the state, the process of its emergence and the main factors that influenced its formation. It is shown that the development of agriculture, social stratification, political centralization, religious and military factors are of great importance in the early formation of states. The process of the emergence of states is studied using the examples of ancient Mesopotamian, Egyptian, Chinese and Indian civilizations. The article also covers the role of the concept of the state in society, its stages of development and its impact on the modern era.